Hipertensi Edukasi dan Pendampingan Self Care Deteksi Dini Pasien Hipertensi Melalui Pengukuran Tekanan Darah di Banjarsari - wahyudi, wahyudi wahyudi (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2024)
Hypertension is an important health problem and one of the chronic diseases with a high incidence and resulting in complications, so cases continue to increase over time. Similarly to what happened in Banyumas district, many chronic diseases are caused by hypertension. One factor is the limited amount of health personnel that requires the involvement of health cadres to empower the public to understand about hypertension. Then another reason, people do not do routine blood pressure tests. This community service activity aims to implement community-based programs so that people can manage their health primarily hypertension and add knowledge and good behavior on how to prevent and treat hypertensive disease in Banyumas district. Self-care activities include weighting, height, and body mass index (BMI) for hypertension screening, followed by 30-hypertensive outpatient. Results of the Pretest knowledge of respondents of the value of knowledge 63,3. The results of the Pre-Test of Knowledge respondents were 63.3. Post-test results were 85.6. Therefore, there was an increase in knowledge by 22.3. Which means that the level of knowledge has increased by 35.23%. Self-care management with compliance taking antihypertensive drugs, a healthy lifestyle that is not smoking is a change in attitude of hypertensive patients that is positive behavior. Based on the research, pre, and posttest results in this community service activity, the results are very effective. It is evident from the enthusiasm of the public when given education about hypertension with the results of the evaluation of activities undergoing increased knowledge. In addition, the independence of the health cadres on early detection of cases of hypertension can have an impact on the improvement of public health levels in Banyumas District